2018
DOI: 10.1016/j.avb.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

“Adding fuel to the fire”? Does exposure to non-consenting adult or to child pornography increase risk of sexual aggression?

Abstract: This article is the first to integrate the vast research literatures on non-consenting adult and on child pornography (also a form of non-consenting pornography) by using the framework of the Confluence Model of sexual aggression. In contrast to the contradictory conclusions reached by various reviewers and commentators who have typically emphasized a particular methodology or parts of the literature, this review finds a great deal of consistency and convergence among the differing methodologies and literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 88 publications
(94 reference statements)
3
58
1
2
Order By: Relevance
“…In examining empirical research on attitudes of porn viewers, viewing porn regularly has been linked with a number of attitudes fostering gender inequality, violence, and/or objectification of women (Demar e, Lips, and Briere 1993). On the one hand, both experimental-and survey-based studies find pornography use runs parallel to hostile masculinity, producing antiwoman sexual aggression (Demar e, Briere, and Lips 1988;Hald and Malamuth 2008;Hald, Malamuth, and Carlin 2010;Hald, Malamuth, and Lange 2013;Kingston et al 2009;Malamuth 2018;Malamuth et al 1995;Malamuth et al 2000;Murnen, Wright, and Kaluzny 2002;Wright and Tokunaga 2015;Wright, Tokunaga, and Kraus 2016). This builds on early experimental studies on exposure to pornography that found decreased support for the women's liberation movement (Zillmann andBryant 1982, 1984) or correlations dependent on the coerciveness or violence in the porn media (Demar e et al 1988;Demar e et al 1993;Garcia 1986;Hald et al 2013).…”
Section: Assessing Impact On Gender Attitudesmentioning
confidence: 86%
See 3 more Smart Citations
“…In examining empirical research on attitudes of porn viewers, viewing porn regularly has been linked with a number of attitudes fostering gender inequality, violence, and/or objectification of women (Demar e, Lips, and Briere 1993). On the one hand, both experimental-and survey-based studies find pornography use runs parallel to hostile masculinity, producing antiwoman sexual aggression (Demar e, Briere, and Lips 1988;Hald and Malamuth 2008;Hald, Malamuth, and Carlin 2010;Hald, Malamuth, and Lange 2013;Kingston et al 2009;Malamuth 2018;Malamuth et al 1995;Malamuth et al 2000;Murnen, Wright, and Kaluzny 2002;Wright and Tokunaga 2015;Wright, Tokunaga, and Kraus 2016). This builds on early experimental studies on exposure to pornography that found decreased support for the women's liberation movement (Zillmann andBryant 1982, 1984) or correlations dependent on the coerciveness or violence in the porn media (Demar e et al 1988;Demar e et al 1993;Garcia 1986;Hald et al 2013).…”
Section: Assessing Impact On Gender Attitudesmentioning
confidence: 86%
“…Much of the research on pornography is situated within what McCormack and Wignall () refer to as a “negative effects paradigm” to study sexual aggression or objectification, and relies on small samples of porn viewers, or larger samples of specific populations (e.g., college students), to measure effects and individual attitudes through lab‐based experiments or correlating pornography use with mediating variables leading to sexual aggression (Kingston et al. ; Malamuth ; Malamuth, Addison, and Koss ; Malamuth et al. ; McKee ; McNair ; Murnen, Wright, and Kaluzny ; Paul and Shim ).…”
Section: Pornography Sexual Aggression and Sexismmentioning
confidence: 99%
See 2 more Smart Citations
“…Although probably as well-known in the field as the Confluence Model-which, despite its shortcomings (see Baer et al, 2015), has been repeatedly shown to predict the target behavior (Malamuth and Hald, 2017;Malamuth, 2018)-the CPT is supported by surprisingly little evidence. While it remains influential in the current discussions over the existence and phenomenology of pornography addiction (Ley et al, 2014;Shor and Seida, 2018), the CPT seems to fail as a conceptual framework to clarify ramifications of adolescent pornography use.…”
Section: Accepted Manuscriptmentioning
confidence: 99%